Heterocycles Synthesis and Biological Activities (IntechOpen, 2020)
Heterocycles have constituted the largest area of research in organic chemistry. These heterocycles play an important role in biochemical processes because the side groups of the most typical and essential constituents of living cells, DNA and RNA, are based on aromatic heterocycles. Many synthetic methods have been developed for the preparation of heterocycles. The recent surge of interest in the chemistry of heterocycles can be explained by their unusual properties and exotic structure. These heterocycles include highly stable aromatic compounds that display physicochemical properties with relevance in the design of new materials. Thus, heterocycles contribute to the development of society from a biological and industrial point of view.